2018
DOI: 10.4018/ijssci.2018100104
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Power and Phase Synchronization in Multi-Trial Speech Imagery

Abstract: Speech imagery is one form of mental imagery which refers to the imagining of speaking a word to oneself silently in the mind without any articulation movement. In this work, electroencephalography (EEG) signals were acquired while speaking and during the imagining of speaking consonant-vowel-consonant (CVC) words in multiple trials of different time frames. Relative powers were computed for each EEG frequency band. It has been observed that relative power of alpha and theta bands was dominant. Phase Locking V… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 21 publications
0
1
0
Order By: Relevance
“…Spagna and coworkers (Spagna et al, 2021) discovered that visual mental imagery engages the left fusiform gyrus, and patients with extensive left temporal damage often have this type of imagery impairment. But speech imagery blocks the alpha and theta band in the left hemispheric frontal and temporal regions (Chengaiyan et al, 2018). Hardwick et al (2018) in their meta-analysis of the brain correlates of motor imagery, observation, and execution of movements found that motor imagery and action observation recruited similar premotor-parietal cortical networks.…”
Section: Mental and Motor Imagery In Neurosciencementioning
confidence: 99%
“…Spagna and coworkers (Spagna et al, 2021) discovered that visual mental imagery engages the left fusiform gyrus, and patients with extensive left temporal damage often have this type of imagery impairment. But speech imagery blocks the alpha and theta band in the left hemispheric frontal and temporal regions (Chengaiyan et al, 2018). Hardwick et al (2018) in their meta-analysis of the brain correlates of motor imagery, observation, and execution of movements found that motor imagery and action observation recruited similar premotor-parietal cortical networks.…”
Section: Mental and Motor Imagery In Neurosciencementioning
confidence: 99%